Implications Legal Reduction of Land Sale and Purchase Value by Land Deed Making Officials at the Request of the Parties to Reduce Land and Building Acquisition Tax in Brebes Regency - Ayuningrum, Anggit Pramesta Wardani; Tri Bawono, Bambang (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This research aims to find out and analyze the validity of the Deed of Sale and Purchase made by reducing the value of the land sale and purchase carried out by the PPAT at the request of the parties to avoid land and building acquisition tax and to find out and analyze the legal implications of the reduction in the value of the land sale and purchase carried out by the PPAT to reduce the land and building acquisition tax in Brebes district. This study uses an empirical legal research method, in this study using primary data in the form of interviews and documentation. Based on the study, it was concluded that 1) The validity of the deed of sale and purchase of land whose value was reduced by the PPAT to avoid BPHTB tax creates a dilemma for the PPAT between fulfilling the client's wishes and maintaining professional ethics. Although this practice is common, it violates tax regulations and the principle of legal certainty. Professional PPATs should reject such requests and consistently apply ethical standards. Prevention through education, supervision and law enforcement is needed to maintain the integrity of the PPAT profession. 2) Legal implications of the reduction in the value of land sales and purchases carried out by PPAT to reduce the tax on land and building acquisition rights in Brebes Regency, namely the reduction in the value of land transactions by PPAT in Brebes Regency to reduce the BPHTB tax has the potential to cause criminal and civil implications for PPAT. In addition, this practice also harms regional income from BPHTB tax. Preventive efforts include socialization, supervision, and law enforcement. Increasing the transparency of land value information and public education are also needed to overcome tax compliance problems.Keywords: Land; Purchase; Reduction; Sale; Transaction.